Accelerator radiation physics for personnel and environmental protection - Cossairt, J. Donald, 1948-; Quinn, Matthew (Radiation and laser safety officer) (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"Providing a vital resource in tune with the massive advancements in accelerator technologies that have taken place over the past 50 years, this book is a comprehensive reference for accelerator designers; operators; managers; health and safety staff; and governmental regulators. Up-to-date with the latest developments in the field, it allows readers to effectively work together to ensure radiation safety for workers, that adequate protection of the environment is achieved, and that adherence to applicable standards and regulations is maintained. This book will also be of interest to graduate and advanced undergraduate students in physics and engineering who are studying accelerator physics"--
Basic radiation physics concepts and units of measurement -- General consideration for acceleration radiation fields -- Prompt radiation fields due to electrons -- Prompt radiation fields due to protons and ions -- Unique low energy prompt radiation phenomena -- Shielding materials and neutron energy spectra -- Induced radioactivity in accelerator components -- Induced radioactivity in environmental media -- Radiation protection instrumentation at accelerators.
OCLC-licensed vendor bibliographic record.
Keywords: Radiation -- Safety measures; Particle accelerators -- Shielding (Radiation); SCIENCE / Physics; SCIENCE / Nuclear Physics